Implementasi Data Mining Prediksi Perminatan Jurusan Siswa pada SMK Negeri 1 Waikabubak dengan Metode Algoritma C4.5 - Marten Sudi; Gergorius Kopong Pati; Lidia Lali Momo (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
Admission of new students to an educational institution is an activity that is always carried out every new academic year, where prospective new students always increase from year to year (Muwardah and Pramunendar, 2015). Admission of students can be held from elementary to middle school, from middle school to high school / vocational school. The focus of this research is the registration of new students at SMK. As is known, SMK is a Vocational High School or abbreviated as (SMK) and where there are many majors provided which ultimately makes prospective new students confused about which major is right for them because will take a long time.. Based on C4.5 as a Classification Algorithm: C4.5 is a popular algorithm for building decision trees. It works by dividing a dataset into smaller subsets based on attribute values, thus forming an easy-to-understand tree structure. Classification results using decision trees provide a clear visualization of the decision-making process and the variables that contribute to student choices.